The Correlation between Glycemic Characteristic and Erythrocyte Indices in Obesity - Dharma Lindarto; Santi Syafril; Dairion Gatot (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Elevated blood glucose level is a major factor in development of diabetic complications due to unfavorable hyperglycemic induced biochemical as well as hematological indices changes. The aim of this study was to evaluate the correlation between glycemic characteristic and erythrocyte indices in obese subjects with different glycemic status.METHODS: Cross cross-sectional study was designed, and 80 obese subjects were enrolled. The correlations between glycemic characteristic (fasting plasma glucose (FPG), postprandial plasma glucose (PPG), hemoglobin A1c (HbA1c) and homeostasis model assessment of insulin resistance (HOMA-IR)) and erythrocyte indices (Hb, red blood count (RBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC)) were evaluated.RESULTS: Of 80 obese subjects with different glycemic status, there were 48 patients with only obesity (HbA1c <5.7%), 19 patients with pre-diabetes (HbA1c 5.7-6.4%) and 13 patients with diabetes (HbA1c >6.4%). Glycemic characteristic and profile lipid (high-density lipoprotein cholesterol (HDL-C), triglycerides (TG)) were differ significantly in the different HbA1c level. Erythrocyte indices were not differ significantly in the different HbA1c level. Partial Spearman's correlation analysis showed that only MCV was significantly correlated with glycemic characteristic of FPG, PPG, HbA1c and HOMA-IR (r=-0.36, p=0.001; r=-0.29, p=0.007; r=-0.27, p=0.014 and r=-0.236, p=0.035; respectively).CONCLUSION: MCV was significantly correlated with glycemic characteristic (FPG, PPG, HbA1C and HOMAIR). Further investigations are recommended.KEYWORDS: MCV, glycemic-characteristic, HbA1c, erythrocyte indices